Phytochemical analysis and cytotoxic effects of mango (Mangifera indica L) kernel on breast cancer cell lines - Abdullah, Al-Shwyeh Hussah (2015)
Breast cancer is a significant cause of morbidity and mortality among women around the world. Currently, anticancer research focuses are on the discovery of alternative therapeutic compounds from natural products. Although numerous study has been done on plants to discover new drugs for the treatment of chronic diseases like cancer, the products of the mango plant species Mangifera indica L. waterlily, particularly the kernel have not adequately investigated. In this study the M. indica waterlily kernel ethanolic extract are investigated to determine its chemical components and anticancer effect. It is postulated that M. indica waterlily kernel extract has antibreast cancer activities through the antioxidant properties of its constituent compounds. Thus, the objective of this study is to determine and characterize the content of the ethanolic M.indica waterlily kernel extract and determine the antibreast cancer effect of the extract. The M. indica waterlily kernel extract was characterized by high performance liquid romatography-mass spectrometry and gas chromatography-mass spectrometry and its antioxidant potentials determined by 2,2-diphenyl-1-picrylhydrazyl and ferric-reducing antioxidant power assays and determination of its thiobarbituric acid reactive substances and glutathione and reactive oxygen species contents. The cytotoxicity ofthe extract on breast cancer MDA-MB-231 and MCF-7 cells and normal breast MCF-10A cells was assessed by neutral red uptake, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, and lactate dehydrogenase release assays and morphological studies, using doxorubicin as the control. The effects of the extract on apoptosis-related markers (Bcl-2, Bax, p53 proteins and Caspase-3, -8 and -9) were also assessed to determine mechanism of cell death. The results showed that M. indica waterlily kernel extract has many bioactive compounds especially phenolics such as phenolic acid, flavonoides and xanthones. When chemical components of the extract was test against the breast cancer cell line, it was shown that mangiferin, rutin, chlorogenic acid and myricetin, but not p-coumaric acid or epigallo-catechin, exhibitedsignificant cytotoxic effects against the breast cancer cell only, not the normal cells. It was therefore assumed that it is the mangiferin, rutin, chlorogenic acid and myricetin content of the M. indica kernel extract that contributed towards the cytotoxicity. The extract has high antioxidant potentials, and induced cytotoxicity in MDA-MB-231 and MCF-7 cells lines in a dose- and time-dependent manner, but was not toxic to the normal breast cells, MCF-10A. It is suggested that the anticancer effect of the M.indica extract is via modulation of redox status through its antioxidant constituents and induction of apoptosis. These findings suggest that M. indica kernel extract, with antiproliferative properties towards cancer cells, while relatively innocuous to normal cells, is a good candidate as an alternative to or for supplementation for current chemotherapies in the treatment of breast cancers, without showing the side-effects associated with these anticancer drugs.